Bilateral Bartonella neuroretinitis in an 11-year-old girl without a history of cat scratches - Akova, Umut; Baskin, Esra; Akova, Yonca (Digital Journal of Ophthalmology, 2026)
An 11-year-old girl presented at Bayindir Kavaklidere Hospital with a 15-day history of progressive bilateral eye redness and vision loss. She reported that over the previous week, her vision had deteriorated significantly. Visual acuities on presentation were 20/200 in the left eye and 20/100 in the right eye. Ophthalmic examination revealed bilateral conjunctival hyperemia, with 4+ cells in the right eye and 3+ cells in the left in the anterior chamber. Intraocular pressure was 15 mm Hg in the right eye and 13 mm Hg in the left eye. Fundus examination demonstrated optic disc hyperemia and swelling bilaterally, accompanied by macular star formation, more pronounced in the right eye (A, arrow), consistent with bilateral neuroretinitis. Optical coherence tomography revealed flattening of foveal contour, central marked retinal thickening, and macular subretinal fluid. The patient reported contact with cats but denied scratches. Serological testing confirmed Bartonella infection, diagnosing Bartonella neuroretinitis. Following consultation with pediatric specialists, she was treated with doxycycline 100 mg twice daily for 12 weeks, along with a single 600 mg dose of rifampin. Additionally, she received a tapering regimen of oral prednisolone, starting at 20 mg daily, tapered to 10 mg over 12 weeks. Topical prednisolone eye drops were administered starting with 8 drops per day and tapered as inflammation subsided. At her 12 weeks’ follow-up, her visual acuity had significantly improved to 20/20 in the right eye and 20/25 in the left eye. The optic disc hyperemia and edema had significantly decreased.